The Effect of Hamburger Strategy in Writing Descriptive Text of the 1st Semester Students of English Department in Nommensen University - Fenty Debora Napitupulu (Universitas Bunda Mulia, 2018)
This study deals with the effect of hamburger strategy on writing descriptive text. Hamburger strategy is a writing organizer strategy that visually outlines the key components of a paragraph. When writing by using hamburger strategy, the students will learn to remember how to build the paragraph and the importance of each component. It was conducted by using experimental quantitative research. The population of this study is the first semester students of English Department Nommensen Medan. The writer takes 50 students as the sample and they are devided into two groups by using random sampling. The first group was group A as Experimental class which is taught by implementing hamburger strategy while the second group is Group B as control class which is taught by using conventional method. Oral test is used as the instrument of collecting the data. This test consists of two types, namely pre-test and post-test. The data were analyzed by using t-test formula. The calculation shows t-observed that is 3. 58, which is higher than t-table that is 1.676 at the level significance (p: 0.05) with the degree of freedom (df) 48. It means that Ha is accepted while Ho is rejected, therefore it is concluded that hamburger strategy significantly affects on writing descriptive text of the first semester students of English Department in Nommensen University Medan academic year 2016/2017. It is suggested for the students of English Department as source of valuable knowledge and information when conducting a research related to the study. It is also suggested that teachers of English subject should implement hamburger strategy as one of alternative in teaching writing to increase students’ writing ability.Keywords: hamburger strategy, writing hortatory exposition text